Incentive systems in a real effort experiment - van Dijk, Frans; Sonnemans, Joep; van Winden, Frans (European economic review, 2001)
In the reported experiment different payment schemes are examined on their incentive effects. Payments based on individual, team and relative performance are compared. Subjects conducted computerized tasks that required substantial effort. The results show that individual and team payment induced the same effort levels. In team production free-riding occurred, but it was compensated by many subjects providing more effort than in case of individual pay. Effort was higher, but more variable in tournaments, while in case of varying abilities workers with relatively low ability worked very hard and drove up effort of the others. Finally, attitudes towards work and other workers differed strongly between conditions.